Insight into the labeling mechanism of acceleration selective arterial spin labeling - Schmid, Sophie (MAGMA, 2016)
OBJECTIVES: Acceleration selective arterial spin labeling (AccASL) is a spatially non-selective labeling technique, used in traditional ASL methods, which labels spins based on their flow acceleration rather than spatial localization. The exact origin of the AccASL signal within the vasculature is not completely understood. To obtain more insight into this, the acceleration selective module was performed followed by a velocity selective module, which is used in velocity selective arterial spin labeling (VS-ASL). MATERIALS AND METHODS: Nine healthy volunteers were scanned with various combinations of the control and label conditions in both the acceleration and velocity selective module. The cut-off acceleration (0.59 m/s(2)) or velocity (2 cm/s) was kept constant in one module, while it was varied over a large range in the other module. With the right subtractions this resulted in AccASL, VS-ASL, combined AccASL and VS-ASL signal, and signal from one module with crushing from the other. RESULTS: The label created with AccASL has an overlap of approximately 50% in the vascular region with VS-ASL, but also originates from smaller vessels closer to the capillaries. CONCLUSION: AccASL is able to label spins both in the macro- and meso-vasculature, as well as in the microvasculature. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10334-016-0596-6) contains supplementary material, which is available to authorized users.